'Buying in' to communicative language teaching: the impact of 'initial' certification courses on the classroom practices of experienced teachers of English. Issue 1 (1st January 2020) - Anderson, Jason
ABSTRACT: This study reports on the impact of an 'initial' certification course (ICC) for English language teachers (the Cambridge CELTA) on the self-reported classroom practices and related beliefs of experienced teacher-participants. Although many participants on such courses are experienced non-native speaker teachers of English (NNESTs), almost nothing is known about the impact of ICCs on their classroom practices. Qualitative data, including questionnaire and interview data, was collected from 29 experienced Egyptian teachers of English 6 months after course completion to understand what changes had occurred in their self-reported classroom practices, their beliefs, and what challenges they had faced interpreting what they had learnt for their own teaching contexts. The data reveals a commitment on the part of most participants to implement the practices imparted on the course, indicating a noticeable shift in beliefs about how languages are learnt and taught towards more communicative, learner-centred practices. It also reveals increases in self-confidence from some participants, both regarding classroom practices and personal status as internationally certified teachers. However, significant variation in self-reported implementation was also found depending on contexts, constraints and challenges, indicating strongly that the communicative practices promoted on 'international' ICCs need adaptation in order for them to work effectively in primary, secondary, tertiary and adult classrooms in the Middle East. Recommendations provided include more discussion, both in inputs and assignments, of issues of how course participants will appropriate what they have learnt on the course for their own classrooms, and the provision of opportunities for peer-support, possibly online, after course completion.